Does Macroeconomics Need Microeconomic Foundations? - Sergio Da Silva (Kiel Institute for the World Economy (IfW), 2009)
The author argues that it is microeconomics that needs foundations, not macroeconomics. Preferences need to be built on biology, and, in particular, on neuroscience. In contrast, macroeconomics could benefit from rationalizations of aggregate economic phenomena by non-equilibrium statistical physics.
Keywords: C82; B41; B22; D87; 330; Microfoundations; neuroeconomics; econophysics; Mikroökonomische Fundierung; Neuroökonomie; Econophysics